Immunoinformatics Predictions on Variable Mycobacterium tuberculosis Lineage 6 T Cell Epitopes and HLA Interactions in West Africa - Marta L. Silva; Nuno S. Osório; Margarida Saraiva (Microorganisms)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a global health challenge. The human-adapted TB-causing bacteria are distributed into ten lineages with distinct global distributions and clinical outcomes. Mtb lineages 4 (L4) and L6 are good prototypes of these differences, because L4 is globally prevalent, whereas L6 is geographically restricted to West Africa and associated with slower disease progression. Given the fundamental role of T cells for the control of TB, we questioned whether Mtb L4 or L6 antigens and HLA interactions would be disrupted in West African hosts. Here, we selected variable and validated antigens and demonstrate their expression during in vivo Mtb L4 or L6 infections. We then compared the predicted number of IFN-γ-inducing and HLA high-binding-affinity peptides in Mtb ancestral, L4, or L6 proteins, considering HLA alleles of high or low frequency in West Africa. Our immunoinformatics approach predicts that non-synonymous substitutions of high variance in Mtb L6 strains diminish binding affinities to HLA alleles prevalent in West African populations, suggesting specific adaptations of these strains to their preferred hosts. Future functional studies will advance our knowledge on lineage-specific evolution and inform strategies to enhance TB control in endemic regions.